2019 IEEE International Conference on Systems, Man and Cybernetics (SMC) 2019
DOI: 10.1109/smc.2019.8913848
|View full text |Cite
|
Sign up to set email alerts
|

Spectral EEG-based classification for operator dyads’ workload and cooperation level estimation

Abstract: There is a growing momentum to design online tools to measure mental workload for neuroergonomic purposes. Most of the research focuses on the monitoring of a single human operator. However, in real-life situations, human operators work in cooperation to optimize safety and performance. This is particularly the case in aviation whereby crews are composed of a pilot flying and a pilot monitoring. The motivation of this study is to evaluate the possibility to apply an hyperscanning approach to estimate the menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Demand manipulations in previous action team experiments have spanned across dimensions including task quantity (Strang et al, 2012), task difficulty (Verdière et al, 2019), time pressure (Cui et al, 2021), demand imbalances (Porter et al, 2010), workload transitions and non-routine events (Jobidon et al, 2006), and asset availability (Knott et al, 2006). For this study, we wanted to manipulate demand (1) at the team-level and (2) in a resource-limited manner (also at the team level).…”
Section: Testbed Design and Developmentmentioning
confidence: 99%
“…Demand manipulations in previous action team experiments have spanned across dimensions including task quantity (Strang et al, 2012), task difficulty (Verdière et al, 2019), time pressure (Cui et al, 2021), demand imbalances (Porter et al, 2010), workload transitions and non-routine events (Jobidon et al, 2006), and asset availability (Knott et al, 2006). For this study, we wanted to manipulate demand (1) at the team-level and (2) in a resource-limited manner (also at the team level).…”
Section: Testbed Design and Developmentmentioning
confidence: 99%
“…However, in the future, we will also explore an alternative study protocol where dyads will go through multiple artificially induced conversation scenarios (e.g., told to argue with each other), and classification methods will be used to assign physiological data to one of the possible scenarios. While less natural than the current protocol, this is likely to provide more balanced data, and classification algorithms are more common than regression algorithms in both studies of physiological synchrony (Hernandez et al, 2014;Konvalinka et al, 2014;Muszynski et al, 2018;Zhu et al, 2018;Brouwer et al, 2019;Verdiere et al, 2019;Darzi and Novak, 2021) and general affective computing (Novak et al, 2012;Aranha et al, 2019). Unrelated to the above classification approach, we may also consider a multi-day protocol where engagement estimation algorithms are trained on data from one session, then tested on data from another session.…”
Section: Classification and Multi-day Scenariosmentioning
confidence: 99%
“…However, while there have been many studies targeting group-level analysis of physiological synchrony (e.g., correlating synchrony and engagement in a large sample), there has been relatively little work on quantifying engagement or other interpersonal states at the level of individual dyads (e.g., tracking interpersonal engagement of a specific dyad over time). A handful of studies have used classification algorithms with a single physiological modality (e.g., electroencephalography alone) to discriminate between two states (e.g., engaged vs. unengaged dyads) ( Hernandez et al, 2014 ; Konvalinka et al, 2014 ; Muszynski et al, 2018 ; Zhu et al, 2018 ; Brouwer et al, 2019 ; Pan et al, 2020 ) with one study discriminating between four affective states ( Verdiere et al, 2019 ). A final study used regression algorithms to map physiological synchrony to self-reported arousal and valence on 1–9 scales using electroencephalography during video watching ( Ding et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study [21] used LabRecorder [20], the main recording application of LSL, to synchronize and centralize the streams of two wireless EEG systems on a network while research participants performed a word-by-word interaction task. LSL-synchronized EEG systems were used in another study [22] to explore the mental workload of one pilot flying and another pilot monitoring during a simulated flight. With the support of cross-platform development and the need for multimodal data streaming, an increasing number of new devices feature an LSL plugin to enable two-way communication between devices with submillisecond timing precision.…”
Section: Have Launched Ambitious Programsmentioning
confidence: 99%